Ensino de psicologia na Escola de Enfermagem Carlos Chagas (1933 - 1962) - Carolina Silva Bandeira de Melo (2010)
The main target of the present dissertation is to learn about the insertion and development of Psychology, as a course subject, into the Nursing Course of the Carlos Chagas Nursing School from 1933 to 1962. Both, when the subject was included in the course and the contextualization of its inclusion have been studied, and information about the Psychology syllabus taught at the Carlos Chagas Nursing Course was researched as well as the information about the teachers who were responsible for that subject within the referred period. The Carlos Chagas Nursing Course was selected for this study due to the fact that it is the oldest institution among the other Nursing courses in the city of Belo Horizonte, besides being one the first Nursing schools founded in Brazil. The theoretical and methodological feedback that guided the research was the historiography and its reflections on the historical study. The sources of documents approached were the School Files kept at the Memory Center of the Nursing School of the Minas Gerais State Federal University (which was initially born from the Carlos Chagas Nursing School). Furthermore, the files of the Alfredo Pinto Nursing School of the Rio de Janeiro State University and the files of the Anna Nery Nursing School of the Rio de Janeiro State Federal University were also investigated. The analysis of the documents unveiled that: 1) Nursing was tuned with the prevailing Brazilian Psychology discourse in that period of time; 2) initially, physicians intermediated the relationship between Psychology and Nursing; 3) the occurrence of educative concepts in Nursing indicated the circulation of theories from Educational Psychology within Health Psychology and vice versa.